2015
DOI: 10.1007/s11051-015-3113-3
|View full text |Cite
|
Sign up to set email alerts
|

Dispersible crystalline nanobundles of YPO4 and Ln (Eu, Tb)-doped YPO4: rapid synthesis, optical properties and bio-probe applications

Abstract: Undoped and Ln 3? (Eu and Tb)-doped crystalline nanobundles of YPO 4 were prepared by a facile microwave-assisted route with water as a solvent and without using any surfactant. TEM investigations reveal that the as-prepared powder consists of lenticular-shaped nanobundles (*100 nm in diameter) made of very small nanorods with diameter less than 10 nm and length varying from 20 to 50 nm. Each nanorod in turn is single crystalline, as revealed by HRTEM imaging. The as-prepared nanobundles are easily dispersible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
(36 reference statements)
3
11
0
Order By: Relevance
“…[ 31b ] The differently functionalized nanoparticles presented negative surface charge (Table S1, Supporting Information) in good agreement with values previously reported for YPO 4 nanoparticles. [ 32 ] Prior to the nanoparticle labeling, the availability of the FA for binding was confirmed by a dot blot using a folic acid specific antibody. While unfunctionalized and APTES modified nanoparticles showed little binding, a significantly increased fluorescent signal was detected for the FA‐modified nanoparticles (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…[ 31b ] The differently functionalized nanoparticles presented negative surface charge (Table S1, Supporting Information) in good agreement with values previously reported for YPO 4 nanoparticles. [ 32 ] Prior to the nanoparticle labeling, the availability of the FA for binding was confirmed by a dot blot using a folic acid specific antibody. While unfunctionalized and APTES modified nanoparticles showed little binding, a significantly increased fluorescent signal was detected for the FA‐modified nanoparticles (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…As the excitation power is sufficiently high, the higher energy level of green fluorescence ( Fig. 8(a)-(c): 13 for the red counterpart.…”
Section: Upconversion Emission Tuningmentioning
confidence: 98%
“…Rare Earth (RE) activated luminescent materials have drawn continued attention in various fields [1][2][3][4][5], due to their unique optical properties arising from their rich energy level structure, narrow excitation/emission bands, long excited state lifetimes, weak background fluorescence, etc [6][7][8][9][10][11]. Recently, most of the attention is focused on nanocrystals for a variety of potential applications especially as luminescent nano-bioprobes [12][13][14]. In comparison with doped nanocrystals, RE-doped microcrystals usually show higher luminescence quantum yields due to the smaller surface-to-volume ratio and less surface defects that act as quenching centers.…”
Section: Introductionmentioning
confidence: 99%
“…It displayed multiple emission peaks at 593, 614, 650 and 691 nm ascribed to the intra-4 f 6 transitions from the lowest excited 5 D 0 level to the 7 F 1 , 7 F 2 , 7 F 3 and 7 F 4 levels, respectively. [47][48][49][50] These results showed that the protein-inorganic Na 5 Yb 9 F 32 nanomaterials displayed good photoluminescence features and their colours could be easily adjusted by using different kinds of lanthanide ions.…”
Section: Materials Advances Papermentioning
confidence: 99%